2017
DOI: 10.3354/dao03112
|View full text |Cite
|
Sign up to set email alerts
|

Disease ecology of Hematodinium perezi in a high salinity estuary: investigating seasonal trends in environmental detection

Abstract: The blue crab Callinectes sapidus has seen a general decline in population levels. One factor influencing mortality is infections by Hematodinium perezi, a dinoflagellate parasite. A 2 yr study was conducted in 2014 and 2015 to monitor H. perezi DNA within the Maryland (USA) coastal bays, comparing seasonal cycles in the abundance of parasite DNA in environmental samples to parasite presence in host blue crabs. A late summer to early fall peak in H. perezi infections in blue crabs was observed, consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Prevalence is generally highest during the fall or early winter when water temperatures are relatively low, and may decline in late winter when temperatures are lowest [ 14 , 15 , 24 ]. Prevalence increases in spring as water temperatures rise, but later declines in summer when temperatures are highest [ 14 , 24 ], although this pattern is not always followed [ 27 ]. Prior to the results of that study [ 27 ], it has been suggested that extreme temperatures could inhibit either transmission or establishment of infection, with optimum temperatures for the pathogen in the moderate range of 15 to 18°C [ 14 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence is generally highest during the fall or early winter when water temperatures are relatively low, and may decline in late winter when temperatures are lowest [ 14 , 15 , 24 ]. Prevalence increases in spring as water temperatures rise, but later declines in summer when temperatures are highest [ 14 , 24 ], although this pattern is not always followed [ 27 ]. Prior to the results of that study [ 27 ], it has been suggested that extreme temperatures could inhibit either transmission or establishment of infection, with optimum temperatures for the pathogen in the moderate range of 15 to 18°C [ 14 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, active infections were observed in all months, and they rapidly developed into highintensity infections when held at 15°C. It is therefore likely that early benthic juveniles respond in a similar manner, and thus likely explains the bimodal peaks in prevalence observed in larger juveniles and adults, and the detection of H. perezi in environmental samples (Pitula et al 2012, Hanif et al 2013, Lycett & Pitula 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Blue crabs were collected in conjunction with the Maryland Department of Natural Resources Finfish Investigation Surveys. These surveys are performed at 20 sites throughout the Maryland Coastal Bays (MCBs) from April through October (2014–2016) using an otter trawl as discussed previously in detail [ 14 , 19 ]. Sampling typically began during the second week of the month and took place over the course of three non-consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism for disease transmission is unknown, though a waterborne infective dinoflagellate stage is currently favored [ 7 10 ]. The peak of disease manifestation varies from host to host, and even between geographic locations within the same host species [ 1 , 11 19 ]. Infection prevalence by season is suggested to be related to various environmental factors such as the salinity, temperature, pH, dissolved oxygen, and chlorophyll a levels in water [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation